Can digital village construction promote sustainable agricultural development in China? - Yuanchun Yu; Routing Zhang (PLoS ONE, 2025)
Agriculture is a major contributor to global greenhouse gas emissions. Consequently, studying the sustainable development of agricultural activities is crucial for achieving the United Nations’ Sustainable Development Goals. Utilizing panel data from 30 Chinese provinces from 2012 to 2022, this study measured the environmental, economic, and social dimensions of sustainable agricultural development (SAD) at the provincial level in China. Employing two-way fixed-effects and mediated effects models, the study empirically examined the driving effect of digital village construction (DVC) on SAD, along with the underlying mechanisms. The results reveal that the overall level of SAD in China has shown a gradual upward trend, although a pattern of higher SAD levels in the eastern regions compared to the west remains evident. DVC was found to exert a significant positive effect on SAD. Crucially, the market-based allocation of factors and agricultural product circulation were identified as significant mediating variables in this relationship. Heterogeneity analysis showed that the promoting effect of DVC is more significant in major grain-producing areas and in regions exhibiting higher SAD levels. Based on these findings, the study proposes targeted policy recommendations to provide practical strategies for different regions to advance DVC, narrow regional disparities, and enhance SAD levels.